2011
DOI: 10.1111/j.1365-2591.2011.01922.x
|View full text |Cite
|
Sign up to set email alerts
|

Intentional re-plantation of a vertically fractured tooth repaired with an adhesive resin

Abstract: • Intentional replantation after repairing fractured fragments with an adhesive resin extraorally is a treatment option. • Long-term follow-up is necessary to evaluate the outcome of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
0
29
0
1
Order By: Relevance
“…Özer ve arkadaĢları 8 yaptıkları bir çalıĢmada vertikal kök kırığı bulunan anterior üst premolar diĢin cerrahi çekimi sonrası kırık parçalarını adheviz simanla yapıĢtırdıktan sonra diĢi reimplante ederek oklüzyonun devamlılığını tekrar sağlamıĢlardır. Benzer yöntemler kullanılarak vertikal kök kırığı tedavileri literatürlerde mevcuttur [9][10][11][12] . Floratos ve Kratchman 13 maksiller ve mandibular molar diĢlerde tamamlanmamıĢ vertikal kök kırığı bulunan diĢlerin cerrahi rezeksiyonla tedavilerini içeren dört vakayı sunmuĢlardır.…”
Section: Discussionunclassified
“…Özer ve arkadaĢları 8 yaptıkları bir çalıĢmada vertikal kök kırığı bulunan anterior üst premolar diĢin cerrahi çekimi sonrası kırık parçalarını adheviz simanla yapıĢtırdıktan sonra diĢi reimplante ederek oklüzyonun devamlılığını tekrar sağlamıĢlardır. Benzer yöntemler kullanılarak vertikal kök kırığı tedavileri literatürlerde mevcuttur [9][10][11][12] . Floratos ve Kratchman 13 maksiller ve mandibular molar diĢlerde tamamlanmamıĢ vertikal kök kırığı bulunan diĢlerin cerrahi rezeksiyonla tedavilerini içeren dört vakayı sunmuĢlardır.…”
Section: Discussionunclassified
“…This resin was chosen because of reports stating that inflammation of periodontal ligament did not occur histopathologically after bonding of the fracture gap with Super Bond [11,13], and also because of a number of clinical reports [5][6][7][8][9] describing good outcomes when Super Bond was used to treat vertically fractured roots. Super Bond uses tri-n-butyl borane as a polymerization initiator, so when it comes in contact with moisture, radicals are generated and polymerization progresses [14].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, if the tooth is single-rooted, the tooth is extracted, and if it has multiple roots, the root involved is resected or hemisection is performed [1][2][3][4]. A number of studies have described efforts to clinically preserve teeth, with particular success reported with resin bonding [5][6][7][8][9]. Sugaya et al used 4-methacryloxyethyl trimellitate anhydride/methyl methacrylate tri-n-butyl borane (4-META/MMA-TBB) resin to bond 23 teeth with vertically fractured roots, performing bonding either through the root canal or with the intentional replantation method, and reported after 6 to 74 months of observation that 18 (78%) of the teeth could be preserved [5].…”
Section: Introductionmentioning
confidence: 99%
“…MTA is a type of calcium silicate cement and is used for various treatments such as direct pulp capping, root-end filling, root canal filling, perforation repair, and apexogenesis 37,38) . However, the application of dental adhesive resins is also expanding to include various treatments such as restoration of fractured roots [39][40][41][42] , root-end fillings 43) , or perforation sealing 44) . Among a plethora of dental adhesive resins, a 4-methacryloxyethyl trimellitate anhydride (4-META)/methyl methacrylate (MMA)-based resin is highly biocompatible, and exhibits excellent bonding and sealing capabilities in wet conditions 45) .…”
Section: Application Of Fgf-2-loaded Polymer Particles To Restorativementioning
confidence: 99%